Autoantibodies to neuronal surface antigens in thyroid antibody-positive and -negative limbic encephalitis. - Tüzün, E; Erdağ, E; Durmus, H; Brenner, T; Türkoglu, R; Kürtüncü, M; Lang, B; Akman-Demir, G; Eraksoy, M; Vincent, A (2011)
BACKGROUND: Thyroid antibodies (Thy-Abs) are frequently detected in various autoimmune disorders in coexistence with other systemic autoantibodies. In association with an encephalopathy, they are often taken as evidence of Hashimoto's encephalitis (HE). However, the presence of Thy-Abs in a cohort of limbic encephalitis (LE) patients and their association with anti-neuronal autoimmunity has not been explored. PATIENTS AND METHODS: We investigated thyroid and anti-neuronal antibodies in the sera of 24 LE patients without identified tumors by cell-based assay and radioimmunoassay and evaluated their clinical features. RESULTS: There was a female predominance in Thy-Ab-positive LE patients. Five of the eight Thy-Ab-positive patients and six of the 16 Thy-Ab-negative patients had antibodies to voltage-gated potassium channel (VGKC), N-methyl-D-aspartate receptor (NMDAR) or undefined surface antigens on cultured hippocampal neurons. There were trends towards fewer VGKC antibodies (1/8 vs. 5/16, P = 0.159) and more NMDAR antibodies (2/8 vs. 1/16, P = 0.095) among the Thy-Ab-positive LE patients; antibodies to undefined surface antigens were only identified in Thy-Ab-positive patients (2/8 vs. 0/16, P = 0.018). There were no distinguishing clinical features between Thy-Ab-positive patients with and without neuronal antibodies. However, patients with anti-neuronal antibodies showed a better treatment response. CONCLUSION: Thy-Abs can be found in a high proportion of patients with non-paraneoplastic LE, often in association with antibodies to specific or as yet undefined neuronal surface antigens. These results suggest that acute idiopathic encephalitis patients with Thy-Abs should be closely monitored for ion-channel antibodies and it should not be assumed that they have HE.